Socioeconomic status in relation to cardiovascular disease and cause-specific mortality: a comparison of Asian and Australasian populations in a pooled analysis. Issue 3 (17th March 2015) - Woodward, Mark; Peters, Sanne A E; Batty, G David; Ueshima, Hirotsugu; Woo, Jean; Giles, Graham G; Barzi, Federica; Ho, Suzanne C; Huxley, Rachel R; Arima, Hisatomi; Fang, Xianghua; Dobson, Annette; et al.
Abstract : Objectives: In Western countries, lower socioeconomic status is associated with a higher risk of cardiovascular disease (CVD) and premature mortality. These associations may plausibly differ in Asian populations, but data are scarce and direct comparisons between the two regions are lacking. We, thus, aimed to compare such associations between Asian and Western populations in a large collaborative study, using the highest level of education attained as our measure of social status. Setting: Cohort studies in general populations conducted in Asia or Australasia. Participants: 303 036 people (71% from Asia) from 24 studies in the Asia Pacific Cohort Studies Collaboration. Studies had to have a prospective cohort study design, have accumulated at least 5000 person-years of follow-up, recorded date of birth (or age), sex and blood pressure at baseline and date of, or age at, death during follow-up. Outcome measures: We used Cox regression models to estimate relationships between educational attainment and CVD (fatal or non-fatal), as well as all-cause, cardiovascular and cancer mortality. Results: During more than two million person-years of follow-up, 11 065 deaths (3655 from CVD and 4313 from cancer) and 1809 CVD non-fatal events were recorded. Adjusting for classical CVD risk factors and alcohol drinking, hazard ratios (95% CIs) for primary relative to tertiary education in Asia (Australasia) were 1.81 (1.38, 2.36) (1.10 (0.99, 1.22)) for all-cause mortality, 2.47(1.47, 4.17) (1.24 (1.02, 1.51)) for CVD mortality, 1.66 (1.00, 2.78) (1.01 (0.87, 1.17)) for cancer mortality and 2.09 (1.34, 3.26) (1.23 (1.04, 1.46)) for all CVD. Conclusions: Lower educational attainment is associated with a higher risk of CVD or premature mortality in Asia, to a degree exceeding that in the Western populations of Australasia.